A survey of the Public Administration Library collection of eleven ASAP member schools in Metro Manila - Pantola, Alicia T. (1996)
This study provides a brief historical background of the eleven ASPAP (Association of Schools of Public Administration in the Philippines) member schools in Metro Manila and the library which serves as a support institution providing reference materials for sound education and research needs. Focus is given to administration and organization, library personnel (qualification of chief/head librarians and the number of staff), library services, technical services, manner of acquisition and mode of ordering library materials, library funds/fees, source of funds, percentage of the total book fund alloted for acquisition of public administration collection, extent of the library collection (by type of materials and by subject-areas) and interlibrary cooperative collection development. Library users evaluation of the accessibility and size of the library with respect to the library users was also gathered. The questionnaire was used to gather data on the above-mentioned concerns.